Temperature, the GacS/GacA system, and host metabolites regulate the type VI secretion system of Pseudomonas syringae pv. phaseolicola - Arvizu-Gómez, Jackeline Lizzeta; Hernández-Morales, Alejandro; Jofre-Garfias, Alba E; Álvarez-Morales, Ariel (Journal of general plant pathology : JGPP, 2013)
The recently discovered type VI secretion system (T6SS) is implicated in the pathogenic and/or virulence processes of diverse bacteria. The expression pattern of the T6SS differs among different organisms and also depends on several environmental factors. We initiated a study of the conditions that influence T6SS gene expression in Pseudomonas syringae pv. phaseolicola NPS3121. Our results indicate that low temperatures and plant extracts impact the expression of T6SS genes and that the process is subject to regulation by the GacS/GacA two-component system.